Semi Regular and semi weak Regular spaces in intuitionistic topological spaces - Hany, Luma S. (University of Thi-Qar Journal of Science, 2013)
The aim of this paper, giving a new definition of semi-Regular and semi weak Regular spaces inIntuitionistic topological space in additional to studying some correlated equation with several example.